Prison, College, and the Labor Market: A Critical Analysis by Formerly Incarcerated and Justice-Impacted Students. Issue 1 (May 2022) - Quach, Khoi; Cerda-Jara, Michael; Deverux, Raven; Smith, Johnny
Enrollment in and navigation of higher learning institutions as a pathway to social mobility remains a significant challenge for many currently and formerly incarcerated people, particularly for those placed under community supervision. This article reviews research on the topic, drawing out key contributory factors and summarizing reform efforts in recent history. We discuss the potential differential benefits of postsecondary educational attainment for formerly incarcerated people and emphasize the need for more research around educational attainment for this population. We also examine effective model programs in the State of California as a way of highlighting the complex and variable nature of the challenges in higher learning for justice-impacted individuals due to their social and supervisory circumstances. These analyses are used as basis for general policy recommendations to provide a stronger foundation for targeted support frameworks and to assist institutional partners working to improve the experience and success of justice-impacted people in postsecondary education. We conclude the article with a critical reflection regarding the institutional function of education in accordance with the current demands of neoliberalism and a concomitant call to action anchored to an alternative vision for a more emancipatory education.